Main issues addressed in the 2014–2015 revisions to the OECD Genetic Toxicology Test Guidelines. (7th March 2017) - Thybaud, Veronique; Lorge, Elisabeth; Levy, Dan D.; van Benthem, Jan; Douglas, George R.; Marchetti, Francesco; Moore, Martha M.; Schoeny, Rita
Abstract : The Organization for Economic Cooperation and Development (OECD) recently revised the test guidelines (TGs) for genetic toxicology. This article describes the main issues addressed during the revision process, and the new and consistent recommendations made in the revised TGs for: (1) demonstration of laboratory proficiency; (2) generation and use of robust historical control data; (3) improvement of the statistical power of the tests; (4) selection of top concentration for in vitro assays; (5) consistent data interpretation and determination of whether the result is clearly positive, clearly negative or needs closer consideration; and, (6) consideration of 3R's for in vivo assay design. The revision process resulted in improved consistency among OECD TGs (including the newly developed ones) and more comprehensive recommendations for the conduct and the interpretation of the assays. Altogether, the recommendations made during the revision process should improve the efficiency, by which the data are generated, and the quality and reliability of test results. Environ. Mol. Mutagen. 58:284–295, 2017. © 2017 Wiley Periodicals, Inc.